Challenges in the delivery of public HIV testing and counselling (HTC) in Douala, Cameroon: providers perspectives and implications on quality of HTC services - Patrice Ngangue; Marie-Pierre Gagnon; Emmanuelle Bedard (BMC, 2017)
Abstract Background The Cameroon government has made HIV testing and counselling (HTC) a priority in its HIV/AIDS strategic plan. However, there is a dearth of literature on the perspectives of providers on the quality of HTC services. The aim of this study was to explore challenges in the provision of HTC services and their implications on quality of HTC services in Douala's district hospitals. Methods Two primary data collection methods supported by the Donabedian's model of healthcare were used to explain the challenges in the provision of HTC services and their implications on quality of HTC services. This consisted of semi-structured individual interviews with 6 nurses and 16 lay counsellors and a non-participant observation of the physical environment for HTC by site. The study sites were the prevention and voluntary testing and counselling centre (PVTCC) of the six district hospitals of the city of Douala. Results The study reveals concerns about confidentiality and privacy during the counselling sessions due to inadequate and limited space. An absence of consent, even verbal, was reported in one PVTCC. There is no specific accredited training curriculum that leads to a formal registration as a PVTCC staff, and some lay counsellors work without training. Lay counsellors carry the burden of HIV counselling, but the majority of them work for many years without remuneration and recognition. Another quality challenge is the high workload in the district hospitals' lab, which leads to long waiting times for HIV test results, thus contributing to failure to return for results. Conclusion The findings of this study highlighted some issues such as lack of adequate space and equipment for HIV testing and counselling that hinder the quality of HTC services and should challenge the health authorities of Cameroon on the need to reorganize HTC services and create a national HIV quality assurance program.